First Trimester Cardiac Biomarkers among Women with Peripartum Cardiomyopathy: Are There Early Clues to This Late-Pregnancy Phenomenon? - Sarma, Amy A.; Hsu, Sarah; Januzzi, James L.; Goldfarb, Ilona T.; Thadhani, Ravi; Wood, Malissa J.; Powe, Camille E.; Scott, Nandita S. (American Journal of Perinatology, 2022)
Objective Whether biomarkers may enable early identification of women who develop peripartum cardiomyopathy (PPCM) prior to disease onset remains a question of interest.Study Design A retrospective nested case–control study was conducted to determine whether first trimester N-terminal pro-B type natriuretic peptide (NT-proBNP) or high sensitivity cardiac troponin I (hs-cTnI) differed among women who developed PPCM versus unaffected pregnancies. Cases were matched to unaffected women by age, race, parity, and gestational age of sample (control A) and then further by blood pressure and pregnancy weight gain (control B).Results First trimester NT-proBNP concentrations were numerically higher among women who subsequently developed PPCM (116 pg/mL [83–177]) as compared with women in control A (56.1 pg/mL [38.7–118.7], p = 0.3) or control B (37.6 [23.3 − 53.8], p <0.05). A higher proportion of women who subsequently developed PPCM (50%) had detectable levels of hs-cTnI as compared with control A (0%, p = 0.03) or control B (18.8%, p = 0.52). Among both cases and controls, hs-cTnI values were low and often below the limit of detection.Conclusion There were differences in first trimester NT-proBNP and hs-cTnI concentrations between women who subsequently developed PPCM and those who did not, raising the possibility the early pregnancy subclinical myocardial dysfunction may be associated with this late-pregnancy disease.Key Points
Keywords: biomarkers; peripartum cardiomyopathy; troponin; natriuretic peptide